The Effect of Packaging, Product Variance, and Brand Equity on Nutella Consumer Trust - Eli Retnowati; Utami Puji Lestari; Rahayu Mardikaningsih; Ella Anastasya Sinambela; Didit Darmawan; Arif Rachman Putra; Samsul Arifin (Cita Konsultindo Research Center, 2021)
The development of global business has also penetrated the culinary world. Various food manufacturers have marketed their products worldwide. One of the global food brands is Nutella. This breakfast product from Italy has been marketing its products for more than 50 years. To be able to continue to operate in global competition, management needs to increase consumer trust in Nutella products. This study aims to determine the effect of packaging, product variants, and brand equity on consumer trust. The population of this research is all Nutella consumers. Researchers used a research sample of 100 respondents. Research data obtained through questionnaire responses. The analysis technique used in this research is multiple linear regression. The role of the existence of packaging has evidence there is to shape consumer trust. Another finding states that there is a real role given by product variant policies to the formation of consumer trust. Consumer trust has also been shown to be affected by the strength of brand equity. The three independent variables used have been shown to have a significant effect on consumer trust.